Предмет: Математика,
автор: gggggggggg2
(3x+2)*(2x+3)-(x+4)*(x-2)=(5x+2)*(x+1)
Ответы
Автор ответа:
0
(6x^2+9х+4х+6)-(x^2-2х+4х-8)=5x^2+5+2х+2
6x^2+9х+4х+6-x^2+2х-4х+8=5x^2+5+2х+2
6x^2+9х+4х-x^2+2х-4х-5x^2-2х=-6-8+5+2
9х=-7
х=-79 или -0,(7)
Ответ: -7/9 или -0,(7)
6x^2+9х+4х+6-x^2+2х-4х+8=5x^2+5+2х+2
6x^2+9х+4х-x^2+2х-4х-5x^2-2х=-6-8+5+2
9х=-7
х=-79 или -0,(7)
Ответ: -7/9 или -0,(7)
Похожие вопросы
Предмет: История,
автор: ulanovvladislav1811
Предмет: Биология,
автор: ggcchvhhvb
Предмет: Информатика,
автор: daniphantom
Предмет: Химия,
автор: Аноним
Предмет: Геометрия,
автор: chelovek4